Kepemimpinan Kepala Madrasah Dalam Meningkatkan Sikap Disiplin Guru Di MTS Swasta Nurussholih Medan Polonia - Citra Malinda Sitorus; Afrahul Fadhilla Daulai; Fachruddin Azmi (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
The progress of a nation cannot be separated from the progress of the world of education. According to Law Number 20 of 2003 concerning the National Education System, article 1 paragraph (1) states that "education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual strength. personality self-control, intelligence, noble morals, as well as skills needed by himself, the nation's community and the state. This research generally aims to describe (1) How the Leadership Role of Madrasah Heads Plays in Improving Teacher Disciplinary Leadership Attitudes at Private MTs Nurussholih Medan Polonia (2 ) What is the attitude of the Madrasah Head in Forming Disciplinary Attitudes of Teachers at Nurussholih Private MTs Medan Polonia (3) What are the Obstacles? and Efforts to Overcome Them Madrasah Heads in Improving Disciplinary Attitudes to Become Effective and Efficient This research is a type of qualitative research with a case study approach. This research was conducted at Nurussholih Medan Polonia Private MTs which is located at Jl. Cempaka No. 20 Karawang Sari Rejo Medan, Medan Polonia District, North Sumatra. The subjects in this study were the Madrasah Head, Deputy Madrasah Head, and Teachers. The techniques used in data collection are observation, interview and documentation techniques. The analysis technique in this study uses data reduction, data presentation and conclusion. Guarantees for the validity of the data in this study are credibility, transferability, reliability, and confirmability. The results of the research show that (1) The leadership of the Head of the Nurussholih Medan Polonia Private MTs Madrasah has seven roles in improving teacher discipline, namely as an educator, manager, administrator, supervisor, leader, innovator and motivator. (2) The attitude of the madrasa head in forming the teacher's attitude is good because the head of the Nurussholih Medan Polonia Private MTs madrasa is able to set an exemplary example for the teachers at the madrasa. (3) The madrasa head's efforts to improve teacher discipline are very strict in terms of teacher attendance, and the problem is that there are still teachers who do not come to the madrasa on time because the distance from home to school is quite far so they lack discipline.